2019
DOI: 10.3390/app9204436
|View full text |Cite
|
Sign up to set email alerts
|

Collapse Responses of Concrete Frames Reinforced with BFRP Bars in Middle Column Removal Scenario

Abstract: Six concrete beam-column frame sub-assemblages reinforced with basalt fiber-reinforced polymer (BFRP) bars in the frame beams were designed to investigate the collapse resistance after a middle column removal. Effect of parameters, including span to depth ratio of frame beams, prestressing, as well as material types of stirrups in the beams, on the collapse resistance of the sub-assemblages, was investigated. Experimental results showed that the initial stiffness of the frame beams was apparently lower due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Remarkably, the FE method has been used in many existing studies to simulate the collapse behavior of buildings. For instance, a number of FE method-based studies have focused on the collapse resistance of structures before the formation of debris [21][22][23][24][25][26][27][28]. In contrast, studies on the collapse debris distribution are relatively limited, mainly due to the high computational cost of the FE simulations for such problems [20,29].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the FE method has been used in many existing studies to simulate the collapse behavior of buildings. For instance, a number of FE method-based studies have focused on the collapse resistance of structures before the formation of debris [21][22][23][24][25][26][27][28]. In contrast, studies on the collapse debris distribution are relatively limited, mainly due to the high computational cost of the FE simulations for such problems [20,29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the robustness of sub-assemblages increased as the span to depth ratio of beams decreased. Kim et al [71] experimentally investigated the influence of anchorage techniques by varying the geometry and amount of CFRP materials on ten beam specimens. That study demonstrated that the full strength of CFRP sheets on the side faces could be achieved only by a combination of CFRP anchors and U-wraps.…”
Section: Sensitivity To Beam Span Length and Shear Strength Of Streng...mentioning
confidence: 99%
“…They are widely used in concrete structures such as bridges, roads, and wharfs [2]. Many experts and scholars have conducted in-depth research and analysis on the failure modes, mechanical properties, and bonding properties of BFRP bar concrete beams [3][4][5][6][7][8]. The low elastic modulus of BFRP bars causes large deformation of the concrete components and an increase of crack widths.…”
Section: Introductionmentioning
confidence: 99%